Agriculture intensification and moisture-induced Thar desert greening: implications for energy balance, socio-economy, and biodiversity - Rahul Kashyap; Jayanarayanan Kuttippurath; Vikas Kumar Patel (GIScience & Remote Sensing)
Despite being the largest biome, landscape dynamics in drylands is largely under-explored. We investigate the changing landscape in the most inhabited desert – the Thar, for last two decades (2001–2020), its drivers, quantification of natural and anthropogenic control, future evolution and potential implications. We employ a suite of advanced statistical and machine learning (ML) techniques on remote sensing and reanalyses data. We find that the Thar desert is greening in recent decades as evident in the increased surface greenness (28.4%), leaf area (21.7%), photosynthesis (33.5%) and productivity (22.9%). Enhanced moisture availability by precipitation (P, 29.7%) and soil moisture (SM, 4.5%) triggers this greening, predominantly in post-monsoon (September–November). This moisture-induced greening of Thar is driven by the westward shift of Indian Summer Monsoon (ISM) rainfall. Partial correlation reveals that SM has a stronger control on vegetation than P and the Granger Causality confirms that SM has a direct causal effect on vegetation in all seasons. The change detection analysis shows an increase in croplands (23.5%) at the expense of shrublands (−5.3%), as there are conversions of barren lands to shrublands and then shrublands to croplands aided by the enhanced water availability from irrigation (12.4% in 2000–2015) through canals and inland water bodies. Random Forest (RF) model reveals that climate change (60.7%) has a greater control on Thar greening than human influence (39.3%). Henceforth, the Thar desert is greening due to enhanced moisture availability and agriculture intensification, which is likely to get amplified in future and might substantially change the landscape of this “great desert” by the end of the 21st century. Greening of Thar can improve the socio-economic scenario and help to attain food security, but can be a great threat for the traditional agropastrolism, indigenous biodiversity and change the regional energy balance.